2018
DOI: 10.1101/305169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biphasic recruitment of TRF2 to DNA damage sites promotes non-sister chromatid homologous recombination repair

Abstract: Summary StatementTRF2 is recruited to damage sites by a two-step mechanism and functions in non-sister chromatid homologous recombination repair Abstract TRF2 is a shelterin component critical for telomere integrity. While TRF2 directly recognizes and binds telomeric repeats, evidence suggests that it also localizes to nontelomeric DNA damage sites. However, this recruitment appears to be precarious and functionally controversial. We find that TRF2 recruitment to damage sites occurs by a two-step mechanism: th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…For this purpose, immunocytochemistry assays were performed to investigate the co-localization of endogenous LAP1, TRF2 and γ-H2AX in HeLa cells’ nuclei in a baseline state and upon a short-term bleomycin exposure (200 µg/mL for 30 min, followed by 6 h of recovery). A general analysis by confocal microscopy revealed that all proteins are located at the expected nuclear compartments irrespective of the experimental condition, wherein γ-H2AX ( Figure 6 A and Figure 7 A) and TRF2 ( Figure 7 A and Figure 8 A) are typically dispersed across the nucleoplasm whereas LAP1 is mostly distributed throughout the NE ( Figure 6 A and Figure 8 A), being consistent with previous descriptions for each protein [ 18 , 22 , 44 , 59 , 60 ]. Regarding their fluorescence intensity in the nucleus, the results indicated that, overall, the abundance of the three proteins augments after cell exposure to the DNA-damaging treatment comparatively to the control group ( Supplementary Figure S4A,C,E ), thus confirming the prior findings ( Figure 2 C, Figure 4 B and Figure 5 B).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…For this purpose, immunocytochemistry assays were performed to investigate the co-localization of endogenous LAP1, TRF2 and γ-H2AX in HeLa cells’ nuclei in a baseline state and upon a short-term bleomycin exposure (200 µg/mL for 30 min, followed by 6 h of recovery). A general analysis by confocal microscopy revealed that all proteins are located at the expected nuclear compartments irrespective of the experimental condition, wherein γ-H2AX ( Figure 6 A and Figure 7 A) and TRF2 ( Figure 7 A and Figure 8 A) are typically dispersed across the nucleoplasm whereas LAP1 is mostly distributed throughout the NE ( Figure 6 A and Figure 8 A), being consistent with previous descriptions for each protein [ 18 , 22 , 44 , 59 , 60 ]. Regarding their fluorescence intensity in the nucleus, the results indicated that, overall, the abundance of the three proteins augments after cell exposure to the DNA-damaging treatment comparatively to the control group ( Supplementary Figure S4A,C,E ), thus confirming the prior findings ( Figure 2 C, Figure 4 B and Figure 5 B).…”
Section: Resultssupporting
confidence: 89%
“…After showing that a protein complex formed by LAP1 and TRF2 occurs in vitro , we investigated the establishment of this interaction in human cells. We hypothesized that it could be constitutively active in the cell or, instead, be triggered by a specific signaling event, more precisely by DDR activation, given the previously reported inhibitory [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and stimulatory [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ] roles of TRF2 as well as the recently suggested involvement of LAP1 [ 29 ] in this biological process. Before directly addressing this question, cellular models of DNA damage induction were developed; these consisted in exposing HeLa cells to different concentrations of H 2 O 2 —a reactive oxygen species (ROS)—or bleomycin—a radiomimetic anticancer drug—for distinct time periods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding this variability, it has become clear that laser microirradiation of the DNA/chromatin have contributed significantly to understanding the DNA damage recognition and repair processes. These studies have involved laser damage and repair in the interphase nucleus ( Truong et al, 2013 ; Wang et al, 2013 , 2014 ; Kim et al, 2015 ; Saquilabon Cruz et al, 2016 ; Kong et al, 2018 ; Murata et al, 2019 ), and on condensed chromosomes in mitosis ( Gomez-Godinez et al, 2010 ; Silva et al, 2013 ).…”
Section: Scissors Iii: Dna Repairmentioning
confidence: 99%